2023
DOI: 10.1108/ecam-09-2022-0870
|View full text |Cite
|
Sign up to set email alerts
|

Measuring sensitivity to change orders in construction projects using eigenvector centrality and radius of gyration

Abstract: PurposeThis paper offers a measure of sensitivity to change orders in the later stage of the construction phase to characterize the distribution of project activities around the time when the project is scheduled to finish.Design/methodology/approachThis paper employs eigenvector centrality to identify the sensitivity of an activity to change orders based on the sensitivity of its neighboring activities. Next, a distance-based measure, called the radius of gyration, is adopted to describe the distribution of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
1
0
1
Order By: Relevance
“…Sensitivity model for construction projects to consider future modifications in the final phases of the project (which are usually more important than the modifications affecting earlier phases). [38] The other research line has shown that 65% of 98 projects experienced cost overruns due to modifications, averaging 8% [39]. This is primarily due to repeated work requests, with only 0.39% attributed to these changes.…”
Section: Description Observations Referencementioning
confidence: 98%
“…Sensitivity model for construction projects to consider future modifications in the final phases of the project (which are usually more important than the modifications affecting earlier phases). [38] The other research line has shown that 65% of 98 projects experienced cost overruns due to modifications, averaging 8% [39]. This is primarily due to repeated work requests, with only 0.39% attributed to these changes.…”
Section: Description Observations Referencementioning
confidence: 98%
“…En el trabajo de Zarghami (2023) se realiza una investigación con la que se propone un modelo de sensibilidad de los proyectos de construcción a contemplar modificaciones futuras en las fases finales del proyecto, dando lugar a mayores problemas que en fases anteriores.…”
Section: Los Modificados De Proyectos En Ingeniería Civilunclassified